First record of the scorpion genus Chactas Gervais, 1844, for Brazil with description of a new species from western State of Amazonas (Scorpiones: Chactidae) - Lourenc¸o, Wilson Roberto; Aguiar, Nair Otaviano; Franklin, E. (Zootaxa, 2005)
A new species, Chactas braziliensis sp. n., is described from Brazilian Amazonia. It can be distinguished from congeners by its small size, a generally darker coloration, a higher number of pectinal teeth, a totally smooth vesicle and its ecological preferences. The genus Chactas Gervais, 1844 is recorded for the first time for Brazil and the Amazon basin. The geographical pattern of its distribution is discussed. Copyright © 2005 Magnolia Press.
Keywords: Chactas; Chactidae; Gervais; Scorpiones